Peripheral Etanercept Administration Normalizes Behavior, Hippocampal Neurogenesis, and Hippocampal Reelin and GABAA Receptor Expression in a Preclinical Model of Depression - Kyle J. Brymer; Erin Y. Fenton; Lisa E. Kalynchuk; Hector J. Caruncho (Frontiers Media S.A., 2018)
Depression is a serious psychiatric disorder frequently comorbid with autoimmune disorders. Previous work in our lab has demonstrated that repeated corticosterone (CORT) injections in rats reliably increase depressive-like behavior, impair hippocampal-dependent memory, reduce the number and complexity of adult-generated neurons in the dentate gyrus, decrease hippocampal reelin expression, and alter markers of GABAergic function. We hypothesized that peripheral injections of the TNF-α inhibitor etanercept could exert antidepressant effects through a restoration of many of these neurobiological changes. To test this hypothesis, we examined the effect of repeated CORT injections and concurrent injections of etanercept on measures of object-location and object-in-place memory, forced-swim test behavior, hippocampal neurogenesis, and reelin and GABA β2/3 immunohistochemistry. CORT increased immobility behavior in the forced swim test and impaired both object-location and object-in-place memory, and these effects were reversed by etanercept. CORT also decreased both the number and complexity of adult-generated neurons, but etanercept restored these measures back to control levels. Finally, CORT decreased the number of reelin and GABA β2/3-ir cells within the subgranular zone of the dentate gyrus, and etanercept restored these to control levels. These novel results demonstrate that peripheral etanercept has antidepressant effects that are accompanied by a restoration of cognitive function, hippocampal neurogenesis, and GABAergic plasticity, and suggest that a normalization of reelin expression in the dentate gyrus could be a key component underlying these novel antidepressant effects.